Frizzled-9+ Supporting Cells Are Progenitors for the Generation of Hair Cells in the Postnatal Mouse Cochlea - Zhang, Shasha; Liu, Dingding; Dong, Ying; Zhang, Zhong; Zhang, Yuan; Zhou, Han; Guo, Lingna; Qi, Jieyu; Qiang, Ruiying; Tang, Mingliang; Gao, Xia; Zhao, Chunjie; et al. (Frontiers in Molecular Neuroscience, 2019)
Lgr5+ cochlear supporting cells have been reported to be hair cell (HC) progenitor cells that have the ability to regenerate HCs in the neonatal mouse cochlea, and these cells are regulated by Wnt signaling. Frizzled-9 (Fzd9), one of the Wnt receptors, has been reported to be used to mark neuronal stem cells in the brain together with other markers and mesenchymal stem cells from human placenta and bone marrow. Here we used Fzd9-CreER mice to lineage label and trace Fzd9+ cells in the postnatal cochlea in order to investigate the progenitor characteristic of Fzd9+ cells. Lineage labeling showed that inner phalangeal cells, inner border cells, and third-row Deiters’ cells were Fzd9+ cells, but not inner pillar cells or GER cells at postnatal day (P)3, which suggests that Fzd9+ cells are a much smaller cell population than Lgr5+ progenitors. The expression of Fzd9 progressively decreased and was too low to allow lineage tracing after P14. Lineage tracing for 6 days in vivo showed that Fzd9+ cells could also generate similar numbers of new HCs compared to Lgr5+ progenitors. A sphere-forming assay showed that Fzd9+ cells could form spheres after sorting by flow cytometry, and when we compared the isolated Fzd9+ cells and Lgr5+ progenitors there were no significant differences in sphere number or sphere diameter. In a differentiation assay, the same number of Fzd9+ cells could produce similar amounts of Myo7a+ cells compared to Lgr5+ progenitors after 10 days of differentiation. All these data suggest that the Fzd9+ cells have a similar capacity for proliferation, differentiation, and HC generation as Lgr5+ progenitors and that Fzd9 can be used as a more restricted marker of HC progenitors.